Ответ:
1) (4;3) 2) (-2;-3)
Пошаговое объяснение:
1) решаем способом сложения(так как есть противоположные y и (-y)
![\left \{ {{x-y=1} \atop {x+y=7}} \right. \left \{ {{x-y=1} \atop {x+y=7}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx-y%3D1%7D%20%5Catop%20%7Bx%2By%3D7%7D%7D%20%5Cright.)
(x+x)+(y-y)=1+7 4-y=1
2x=8 -y=1-4
x=4 -y=-3
y=3
2) тоже решаем способом сложения, ибо есть 3x и -3x
![\left \{ {{3x-8y=18} \atop {-3x+4y=-6}} \right. \left \{ {{3x-8y=18} \atop {-3x+4y=-6}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B3x-8y%3D18%7D%20%5Catop%20%7B-3x%2B4y%3D-6%7D%7D%20%5Cright.)
(3x-3x)+(-8y+4y)=(18-6) 3x+24=18
-4y=12 3x=18-24
y=-3 3x=-6
x=-2